Pelatihan Pembuatan Pembukuan Sederhana Bagi UMKM di Kelurahan Srengseng, Kembangan, Jakarta Barat - Budyastuti, Triyani; Dirman, Angela (Politeknik Penerbangan Indonesia Curug, 2024)
Bookkeeping is a very important part of running a business. There are many important benefits of bookkeeping for business development. By keeping neat and organized financial records, the business can avoid losses or even bankruptcy. Bookkeeping helps map the amount of profit/loss, identify every transaction made, and see the financial condition and taxation of the business that can be used as material for business assessment. Simple records are very influential on business development. Through bookkeeping, MSME owners can see the condition and development of the business, including the company's profits and losses. With this, bookkeeping can be used as a benchmark in designing future business strategies. The community service was held in Srengseng Village, West Jakarta, using the question and answer method. The results of this community service are expected that the participants will gain knowledge about the importance of bookkeeping in their business activities and can apply it in real life.